SIKAP KAMANDIRIAN BELAJAR SISWA DI SEKOLAH DASAR - Handoko Aji Wardana; Sigit Arvianto; Nurhayati Nurhayati (Elementary School and Education Journal, 2026)
This study aims to analyze students’ learning independence attitudes in elementary school. The research employed a quantitative descriptive approach and was conducted at SD Negeri Pengabean 02, Brebes Regency. The research subjects consisted of 21 fifth-grade students in the odd semester of the 2024/2025 academic year. Data were collected using a learning independence questionnaire based on a Likert scale. Data analysis was carried out using IBM SPSS Statistics version 25, which included item validity testing, reliability testing, and descriptive analysis. The results of the validity test showed that all 10 questionnaire items were valid, while the reliability test yielded a coefficient value of 0.803, which exceeded the minimum alpha value (α = 0.50), indicating that the instrument was reliable. The descriptive analysis results revealed that students’ learning independence, measured through the indicators of initiative, self-confidence, and responsibility, achieved an average score of 3.13, categorized as “Good.” Therefore, the learning independence instrument is appropriate for use in the learning process to support and enhance students’ learning motivation.